Demythization of the socialist ideal in Jedlicka's prose Midway upon the journey of our life - Rezacova, Meda Bara (Bohemica Olomucensia, 2020)
The analysis focuses on the relation between the compositional and shaping processes of Jedlicka's prose and their function to reflect and deconstruct the socialist ideal. It does not seek to uncover detailed intertext links, but instead the analysis concentrates on Jedlicka's ideal and idyllic thematic. The analysis uses Macura's concept of the socialist ideal and Bachtin's idyllic chronotope in relation to the character of the text as ``witness testimony about the period.''
Keywords: idyll; myth; Josef Jedlicka; socialist ideal; Kde zivot nas je v puli se svou pouti; demythization; deconstruction